Conceptual principles of state policy of regulation of development of public-private partnerships - Bak, N.; Nikiforov, P.; Zhavoronok, A.; Marych, M.; Marusiak, N. (Cuestiones Políticas, 2022)
The purpose of the proposed research is to form conceptual state policy foundations of regulating public-private partnerships development of countries with economies in transition. The need for substantiation of the regulating state policy of public-private partnership development in the transition economy and transformation processes has determined the topic relevance. The development of theoretical foundations for the state policy is based on systemic and institutional methodological approaches. There were used the method of comparative analysis, statistical analysis, structuring, method of abstraction and formalization. It has been determined that insufficient activity of countries with economies in transition in the public-private partnership projects implementation is due to imperfect legal framework, lack of clarity in the distribution of risks between agreement participants, political crisis and instability, lack of a unified state policy to develop partnerships. The principles of promoting the public-private partnership relations in countries with economies in transition have been identified, which include the formation of advanced legal mechanisms and systems of regulatory bodies, that monitor the public-private partnership implementation; stakeholder support by taking into account private interests, public authorities and end users; careful business partners selection. Basic determinants and a set of conceptual requirements for policy formation have been formed.
Keywords: investment; state regulation; state policy; public administration; public-private partnership